PENGEMBANGAN MULTIMEDIA INTERAKTIF PADA MATERI INDONESIAKU KAYA BUDAYA BERBASIS KEARIFAN LOKAL DI KABUPATEN KEDIRI BAGI SISWA KELAS IV SDN SUMBEREJO 1 - Permatasari, Meilina; Ilmawati Fahmi Imron; Karimatus Saidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the fact that conventional classroom learning often makes students feel bored and unable to understand the material presented. This causes learning to be ineffective and the interaction between teachers and students to be passive. Many students have difficulty understanding the material, as seen in the results of the final assessment on the material